The lost heir: C. Claudius Marcellus in Augustan poetry - Harrison, Stephen (Phaos: Revista de Estudos Clássicos, 2017)
C. Claudius Marcellus (42-23 BCE), Augustus' nephew, son-in-law and one-time destined successor, died at a tragically early age. This paper considers the interesting and diverse traces of his short career and premature end to be found in the Latin poets Vergil, Horace and Propertius and in the Greek epigrammatist Crinagoras.